Reimagining Elizabeth Alexander’s “The Antebellum Dream” through the Lens of Social Practice Theory - Shakir, Raghad; Hadaegh, Bahee (Research Journal in Advanced Humanities, 2025)
The present paper aims to examine Elizabeth Alexander’s The Antebellum Dream Book through the prism of Dorothy Holland’s ‘Social Practice Theory’ in an attempt to unravel how African American identity is built, disintegrated, and repossessed both as a legacy of the past and part of history and culture. The close examination of important poems like “Fugue”, “Visitor”, “Race”, and “Early Cinema”, underscores how Alexander has merged the memory, geography, and the surreal imagery to criticize and redefine the Black identity as a reaction to slavery, migration, and racial violence. Besides being a poetic record of trauma and struggle, the collection is also a place of active cultural formation and the construction of subjectivity. The paper illustrates how the poetic voice of Alexander involves collective memory, disrupts the dominant racial master narratives, and puts Black body and voice in place as both objects and agents of change through a socio-historical approach. In conclusion, the paper establishes the relevance of the anthology as a crucial literary place of expression of identity (both Black and personal), agency, recovery, and movement within the intersection of past trauma and the future